IMPLEMENTASI SQ (SPIRITUAL QUOTIENT) MELALUI POLA PIKIR DALAM MENATA KEPEMERINTAHAN YANG BAIK - ', Ahmad Fauzi ' (JIANA ( Jurnal Ilmu Administrasi Negara ), 2020)
Implementasi SQ (Spiritual Quotient) Melalui Pola Pikir dalam Menata Kepemerintahan Yang Baik. Spiritual values are very easy to say, talk about and write down, but are very difficult to realize or practice. These values are sourced from religious values such as honesty, caring, transparency, responsibility, courage, justice and many others. For example, we have to be honest if we are suspected of being infected by the Corona-19 Virus pandemic, we don't have to be ashamed to report ... We have to care about each other in handling the outbreak, about financing that must be transparent and so on. Because there are indications from certain elements who are not responsible in handling these cases at the field level. Likewise with other values such as responsibilities based on the values of Pancasila, when they want to do a Lockdown, then is the government ready with logistics or food stock? which is the basic needs of citizens? because if this is not done with careful planning, it will have an impact on the deterioration of the nation's economy. This is where Spiritual values are needed namely Ya Mu'min (honest) ,, ya Rahman (caring) and Ya Wakiil (Responsibility). But in its operation, these values are still biased, some betrayed, such as the theft of tens of thousands of masks in Cianjur regency, West Java. Personal protective equipment is limited to various hospitals in the country, blaming each other, saying offensive to the public and so forth. This condition is clearly very influential when it will realize good and clean governance (Good and Clean Governance). This is interesting to study and discuss related to the implementation of SQ (SPIRITUAL QUOTIENT).